Turkish foreign policy at the nexus of changing international and regional dynamics. (2nd January 2016) - Oğuzlu, H. Tarık
ABSTRACT: After examining the causes of Turkey's failure to help secure a benign environment in its neighborhood during and after the so-called Arab Spring, this article tries to answer how foreign policy dynamics played a role between the two parliamentary elections in Turkey held in June and November 2015 respectively. Another question is whether foreign policy developments taking place in Turkey's neighborhood, particularly in the wider Middle Eastern region, will drive Turkey closer to its Western partners in the post-election era. Whether Turkey's rediscovery of the Western international community will be long-term or conjectural development, given its growing security challenges, warrants a closer attention.